Four-leg active power filter control with SUI-PI controller - Mohamed M. El-sotouhy; Ahmed A. Mansour; Mostafa I. Marei; Aziza M. Zaki; Ahmed A. EL-Sattar (Institute of Advanced Engineering and Science, 2021)
Four-leg active power filter is considered one of the greatest vital active filters that are frequently used in industrial applications, especially those that need to be controlled in each individual phase. Also, to control the neutral current that created because of a lot of unbalanced and non-linear loads. In this paper, the used active filter was controlled by a proposed control method which can achieve simplicity and intelligence at the same time. The novelty of this paper is using the proposed controller with Four-leg active power filter. This controller relies on instantaneous reactive power theory, which used to create the required currents that are injected into the network via the used active filter to remove the problems created by unbalanced and non-linear loads. It is also maintained that the current source a pure sinusoidal wave. The system is implemented on MATLAB/Simulink. The simulation results proved the preference of the proposed controller than the conventional proportional-integration controller, where it reduced the percentage of total harmonic distortion for the current source.